Boundary Layer Characteristics over Aindanda Low-Mountain Pass of Kathmandu Valley, Nepal - Shrestha, Saraswati; Shrestha, Sajan; Maharjan, Sangeeta; Regmi, Ram P. (Journal of Institute of Science and Technology, 2015)
The early monsoon time boundary layer characteristics prevailing over Aindanda low-mountain pass of Kathmandu valley has been continuously monitored for the period of 11 to 24 June 2013. The study reveals that the Aindanda pass channels regional air masses from the western neighboring valley up into the Kathmandu valley as westerly/ northwesterly winds during the daytime whereas it drains air mass out of the valley during night-time. The speed of the westerly/northwesterly wind over the pass often exceeds 6.5 ms-1 during the late afternoon. Nighttime mixing layer height (MLH) was highly fluctuating with an average around 300m whereas daytime MLH was suppressed limiting it in between 290-450m above the ground in early part of the day but reduced to 210-270m during the late afternoon. Comparison of diurnal variation of mixing layer height at Aindanda with that of the central area of the valley floor strongly suggests that air mass intruding into the Kathmandu valley through this pass is a cool density flow over the weakly stratified mixed layer of valley. The structure of the wind channeled through this pass indicates the possibility of making hydraulic jump in the western part of the Kathmandu valley, particularly, during the late afternoon time. Journal of Institute of Science and Technology, 2015, 20(2): 22-30